N‐degron specificity of chloroplast ClpS1 in plants. Issue 9 (20th April 2019) - Montandon, Cyrille; Dougan, David A.; van Wijk, Klaas J.
Abstract : The prokaryotic N‐degron pathway depends on the Clp chaperone‐protease system and the ClpS adaptor for recognition of N‐degron bearing substrates. Plant chloroplasts contain a diversified Clp protease, including the ClpS homolog ClpS1. Several candidate ClpS1 substrates have been identified, but the N‐degron specificity is unclear. Here, we employed in vitro ClpS1 affinity assays using eight N‐degron green fluorescence protein reporters containing either F, Y, L, W, I, or R in the N‐terminal position. This demonstrated that ClpS1 has a restricted N‐degron specificity, recognizing proteins bearing an N‐terminal F or W, only weakly recognizing L, but not recognizing Y or I. This affinity is dependent on two conserved residues in the ClpS1 binding pocket and is sensitive to FR dipeptide competition, suggesting a unique chloroplast N‐degron pathway. Abstract :